Revealing the Character of Gunungsari in the Tyasing Utomo Script in Wayang Topeng Jatiduwur - Rachmalia Ayu Agustine Pratiwi; Suryandoko, Welly (Solah, 2025)
This research discusses the character of Gunungsari through the analysis of the Tyasing Utomo script in Wayang Topeng Jatiduwur (Jatiduwur Mask Puppet). This is motivated by the lack of understanding of Jatiduwur artists towards the character of Jatiduwur Mask Puppet. The problem of this research is how the character of Gunungsari if analyzed through the Tyasing Utomo script. The purpose of this research is to describe the character of Gunungsari through the Tyasing Utomo script. This research uses qualitative methods with data collection techniques in the form of interviews, observations, and documentation in the form of literature, videos, photos, and audio recordings. The results showed that Gunungsari has characters such as assertive, responsible, loyal, self-respecting, firm, brave, and unyielding. Gunungsari is described as having an ideal body portion with a dashing, agile, and handsome physique. Gunungsari in Tyasing Utomo has an important role in the unification of Panji Asmarabangun and Dewi Sekartaji.